Pengaruh Penerapan Model Pembelajaran Snowball Throwing Terhadap Hasil Belajar Siswa Kelas X IPS SMA Negeri 1 Randangan - Hermin Hermin; Sri Maryati; Rusiyah Rusiyah (Geosfera: Jurnal Penelitian Geografi, 2026)
This study aims to analyze the effect of the Snowball Throwing learning model on the cognitive learning outcomes of Geography students of class X IPS on the Basic Knowledge of Geography material at SMA Negeri 1 Randangan. The study used a quantitative approach with a quasi-experimental design of the pretest-posttest control group type. The experimental class followed the Snowball Throwing learning model, while the control class used lectures and questions and answers. The results showed that the improvement in learning outcomes in the experimental class was better than the control class. The N-Gain value of the experimental class was in the high category, while the control class was in the medium category. This difference indicates that learning that provides space for students to formulate questions, discuss, and answer friends' questions is able to strengthen conceptual understanding better than one-way learning. These findings confirm that Snowball Throwing not only improves learning outcomes, but also encourages activeness, academic communication, and student involvement in the geography learning process. Thus, this model can be considered as an alternative learning method for Geography material that requires conceptual understanding, interrelationships between phenomena, and more active reasoning.